Factors Influencing Consumer Satisfaction: An Analysis of Consumer Electronics - Odebunmi Abayomi Tunde; Oh Zi Jian; Tianyu Wen; Wong See Khee; Qiong Wu; Yuchun Wu; Yucong Xi; A. J. Ali; Daisy Mui Hung Kee (Asia Pacific Journal of Management and Education (APJME), 2025)
Consumer satisfaction is a crucial determinant of brand success, particularly in the competitive consumer electronics industry. This study examines the key factors influencing consumer satisfaction with Huawei gadgets, focusing on brand loyalty, technological innovation, product quality, and service quality. Using a quantitative approach, data were collected through an online survey distributed via Google Forms to 150 respondents who had purchased and used Huawei devices. Convenience sampling was employed to reach a diverse group of consumers. A five-point Likert scale was used to measure satisfaction levels. The regression analysis revealed that brand loyalty (? = 0.428, p 0.05) and product quality (? = 0.218, p 0.05) have a positive and significant impact on consumer satisfaction, supporting H1 and H3. However, technological innovation (? = 0.90, p 0.05) and service quality (? = negative, p 0.05) did not exhibit significant relationships with consumer satisfaction, leading to the rejection of H2 and H4. The adjusted R² value of 0.285 suggests a moderate model fit. These findings emphasize the importance of strengthening brand loyalty and maintaining high product quality to enhance consumer satisfaction. Future research should explore additional factors such as pricing and marketing strategies to provide a more comprehensive understanding.